Penerapan Model Pembelajaran Kooperatif Tipe Picture And Picture Untuk Meningkatkan Hasil Belajar Matematika Kelas IV MI Tuhfatut Tholibin - AlAyubi, Sholahudin; Zainal, Zainal; Hasana, Hidayatul (FAKULTAS TARBIYAH INSTITUT AGAMA ISLAM SULTAN MUHAMMAD SYAFIUDDIN SAMBAS, 2024)
This research aims to describe the application of the picture and picture cooperative learning model to improve the learning outcomes of MI Tuhfatut Tholibin students for the 2024-2025 academic year in mathematics learning about plane figures. Mathematics is often considered a difficult subject. In addition, the use of learning models and media that are inappropriate and less varied, which causes low student attention and affects their learning outcomes. Therefore, more effective learning methods and media are needed to improve learning outcomes. One solution that can be implemented is the use of a picture and picture type cooperative learning model. This type of research is classroom action research (PTK). The instrument used in this research is data on student learning outcomes carried out in cycle 1 and cycle 2. The results of the research show that the use of the picture and picture type cooperative learning model in mathematics learning can improve the learning outcomes of class IV students at MI Tuhfatut Tholibin. This is shown by an increase in student learning outcomes from pre-cycle to cycle II. The average class score obtained in the pre-cycle was 55.5 and classical completeness was 33%. In cycle I, the average score obtained by students was 71 while classical completeness was 66%. In cycle II, the average score obtained by students reached 91 while classical completion reached 100%. In conclusion, the use of the picture and picture cooperative learning model can improve student learning.